INVENTARISASI KEGIATAN PERTANIAN DI KABUPATEN KUTAI BARAT - Karmini, Karmini (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
Inventory of Agricultural Activities in West Kutai Regency. The aim of this study was to inventory of agricultural activities in Kutai Kartanegara Regency. This study covered economic activities at agriculture sector of paddy, food crops, horticulture crops, estate, forestry, livestock, and fisheries. Data were collected from Statistics of West Kutai Regency.  The descriptive analysis method was applied to inventory some agricultural activities. In study location, there are farming activities which developed consist of wetland paddy and dryland paddy, 6 kinds of food plants, 10 kinds of vegetables, 19 kinds of fruits.  Also, animal husbandry 7 kinds livestock,  fishing culture and fishing catch. The other developed activities is processing timber and non timber forest products.